Intelligent decision support feedback using Multi-Agent System in a defence maintenance environment. (15th January 2008) - Haider, Kamal; Tweedale, Jeffrey; Jain, Lakhmi C.; Urlings, Pierre J.M.
Safety and Airworthiness of airborne platforms rest heavily on the maintainability and reliability to maximise the availability and reduce logistics down time. Most of the test and maintenance data currently produced is either paper-based or discarded and generally fails to provide preventive analysis. Improvements could be made by creating an expert system using intelligent agents. Data Mining techniques and intelligent agents could be employed to create an expert system within the Integrated Logistics Support (ILS), thereby creating a feedback mechanism. This concept would develop into an Intelligent Decision Support System (IDSS) that extrapolates forecasts and warnings. This paper presents the design and development of that agent-based Intelligent Decision Support System (IDSS).